Analysis of Water Availability of Madi Irrigation Network - Pradanapa, Permada Garah; Soeryamassoeka, S. B.; Yulianto, Eko (Fakultas Teknik Universitas Tanjungpura, 2024)
This research analyzes the water availability of the Madi Irrigation Network through detailed assessments of evapotranspiration and discharge data from 2008 to 2019. The study reveals significant seasonal and inter-annual variations in evapotranspiration rates, which typically increase during warmer months and decrease in cooler periods. This fluctuation is closely linked to climatic conditions, influencing agricultural water demand. Monthly discharge data further illustrates these variations, showing high discharge rates in the rainy season (e.g., January and December) and lower rates during drier periods (e.g., August and September). The 80% dependable discharge rates reflect similar seasonal trends, with notable peaks and troughs correlating with rainfall patterns. These insights underscore the importance of adaptive water management strategies to optimize irrigation practices, manage water resources effectively, and address the impacts of climate variability. By understanding these patterns, water managers can better plan for periods of surplus and scarcity, enhancing agricultural productivity and sustainability.Keywords: Water Availability, Irrigation Madi, Irrigation Management, Water Management, Agricultural Water Demand.